2010
DOI: 10.1021/cb9002656
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Mechanisms of Resistance to Small-Molecule Protein Kinase Inhibitors

Abstract: Protein kinases have emerged as one of the most frequently targeted families of proteins in drug discovery. While the development of small-molecule inhibitors that have the potency and selectivity necessary to be effective cancer drugs is still a formidable challenge, there have been several notable successes in this area over the last decade. However, in the course of the clinical use of these inhibitors, it has become apparent that drug resistance is a recurring problem. Because kinase inhibitors act by targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 103 publications
1
60
0
2
Order By: Relevance
“…Але та незначна кількість препаратів, які на сьогодні є апробовани-ми [8,9], мають низку недоліків, серед яких індивідуальна гіперчутливість, виникнення резистентності через мутації генів рецепторів-мішеней як наслідок високої молекулярної специфічності препарату, органоспецифічна токсичність, зумовлена функціонуванням ре-цептора, що блокується [5,8,10].…”
Section: встановлено що похідні дигідропіролу -5-аміно-4-(13-бензотunclassified
“…Але та незначна кількість препаратів, які на сьогодні є апробовани-ми [8,9], мають низку недоліків, серед яких індивідуальна гіперчутливість, виникнення резистентності через мутації генів рецепторів-мішеней як наслідок високої молекулярної специфічності препарату, органоспецифічна токсичність, зумовлена функціонуванням ре-цептора, що блокується [5,8,10].…”
Section: встановлено що похідні дигідропіролу -5-аміно-4-(13-бензотunclassified
“…First, clinical development of vemurafenib revealed that a large number of patients with BRAFV600E mutation had primary or acquired resistance to the RAF inhibitor. Acquired resistance does not seem to develop as a result of mutation of "gatekeeper" residues in BRAF itself, as occurs in resistance to BCR-ABL and EGFR inhibitors (5), but from activation of other proteins in the same or parallel signaling pathways (6). Two of the most common resistance mechanisms involve mutation in the NRAS gene and upregulation of PDGFRb expression (7).…”
Section: Introductionmentioning
confidence: 99%
“…The nitrophenylalanine occupies the adenine-binding pocket, but does not mimic the adenine hydrogen bonding pattern observed for MC4 and most ATP-competitive kinase inhibitors (Krishnamurty and Maly, 2010). When compared to the positioning of the pyrazine group in MC4b, the nitrophenylalanine building block does not bind as deeply into the pocket (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Rather, our structural and biochemical data indicate that MC25 resides 6.7 Å angstroms from Thr338 and that its affinity for Src derives from additional electrostatic interaction between the nitrophenyl group and catalytic Lys295, thereby explaining how MC25 binding is not perturbed by the T338I mutation. This shallow positioning in the nucleotide binding site and interaction with Lys295 are unusual, as most small molecule kinase inhibitors make a characteristic set of hydrophobic and hydrogen bond interactions that mimic the adenine ring of ATP (Krishnamurty and Maly, 2010). An exception are inhibitors like the 5′-fluorosulfonylbenzoate derivatives of the pan-SFK inhibitor PP1 that covalently attach to the catalytic lysine (Gushwa et al, 2012).…”
Section: Discussionmentioning
confidence: 99%